Results of the tectonic stress study of the Northern Eurasia regions - L. A. Sim; A. V. Marinin; G. V. Bryantseva; N. A. Gordeev (Геодинамика и тектонофизика)
The article presents the results obtained by field tectonophysical methods applied to study tectonic stresses of the Northern Eurasia regions, including young and ancient platforms (West European, Timan–Pechora, Turan, West Siberian, East European, and East Siberian) and orogenic frame structures (Caucasus, Northern Tien Shan, Mongolia-Okhotsk system of mesozoids, and Sakhalin Island). Tectonic stress reconstructions provided the basis for analysing the influence of spreading in the North Atlantics and the Arctic on the stress state of the platforms in Northern Europe. A spatial boundary of the influence goes approximately along the margins of the Fennoscandian shield and the Russian plate in the north. Further southwards, the boundary is submeridional and extends from the western wing of the Byelorussian anteclise almost to the Eastern Carpathians. The stress reconstructions for this boundary show the WNW and W-E-trending axes of compression. The boundary line does not coincide with the Teisser-Tornquist line that represents the boundary between the platforms with heterochronous basements. However, it correlates well with heat flow anomalies. The boundary area is confined to the Baltic coast [Sim, 2000. Along the boundary area, near the Baltic Sea, there is an area wherein faulting is mainly caused by extension [Sim, 2000. In this setting, helium permeability is the highest, as shown by the crust map of the European part of the USSR [Eremeev, 1983. Extension in this area is probably related to formation of young grabens in the Baltic shield. Changes in the compression axis orientation may be due to the alternating activations of the grabens in the submeridionalBotnicGulf and the latitudinalGulf of Finland. Reconstructions for individual faults show contradictions in the directions of shear displacements: both right- and left-lateral displacements are possible on the same fault segments, and the axes of compression can have either latitudinal or meridional orientations. The focal mechanisms of the Osmussaar andKaliningrad earthquakes (meridional and latitudinal axes of compression, respectively) give evidence of specific current neotectonic stresses in this area. Another zone is distinguished at 52°N from the above-described area. It is mainly sublatitudinal and detected along the southern flank of the Byelorussian anteclise. Further to the east, its orientation changes to SSW, and it roughly follows the SW boundary of theVoronezh anteclise. Reconstructions for the Ukrainian Shield, located south of this zone, show mainly the unstable orientations of the axes of compression. For the platforms inNorthern Eurasia, the tectonophysical methods reconstructed neotectonic stresses in the structures formed under the influence of intraplatform tectonic stresses. These are the residual gravitational horizontal compression stresses released by long-term denudation and uplifting of the structures, including the Khibiny massif of the Baltic Shield, theOlenek and Munsky massifs of the East Siberian platform. These structures are composed of the ancient Archaean-Proterozoic rock complexes, which have been subjected to predominantly vertical displacements for a long time, from the Paleozoic to the modern stage. Special attention should be given to the tectonic stresses ofSakhalin located at the boundary between the Eurasian and North American lithospheric plates. At the edges of these two largest plates, there are the Amur and Okhotsk microplates separated by theCentral Sakhalin fault, as described in some publications. Neotectonic stress reconstructions forSakhalinIsland show sublatitudinal compression and submeridional extension in the common stress field of shearing. The tectonophysical studies show that the neotectonic stresses differ in large structures: horizontal compression and shearing are typical of the uplifts (Kola Peninsula, Tien Shan, Sakhalin), while horizontal extension and extension with shearing are characteristic of depressions (Kandalaksha graben, depressions of theTatarGulf and theSea ofOkhotsk). Our studies provide the data on spacious ‘white spots’ in the modern stress maps ofNorthern Eurasia. The stress reconstructions for practically all the studied structures show that shearing is the dominant geodynamic regime in the study region.